DETERMINAN DEFORESTASI NEGARA-NEGARA DI KAWASAN ASIA TENGGARA PERIODE 2008-2015 - Handalani, Radite Teguh (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
This study aims to analyze the process of changing forest area or deforestation that is multidimensional and complex, encompassing economic aspects, aspects of governance, social and demographic aspects and physical and environmental aspects represented by 15 independent variables in 10 countries in Southeast Asia in the year period 2008-2015. The analysis and study besides relying on the theoretical foundation and previous research also included several variables that describe the complexity and multidimensional changes in forest area. However, these efforts are often constrained by incomplete data and data reliability. In contrast to some previous studies which focused more on economic aspects or aspects of population increase that affected changes in forest area. This research also includes aspects of governance and social and demographic aspects as well as environmental aspect which are expected to complement the spectrum and study of the problems of deforestation and forest degradation. The method used in this study uses pooled least squares and a series of tests to produce the best model specifications and estimators. In research that uses a 95% confidence level on p-value at a value of Î± = 0.05, it was found that from 15 variables there were only 6 (six) variables that significantly affected the increase in the human development index.